The impact of generative artificial intelligence on management consulting work processes and productivity - Ahola, Konsta (My University, 2026)
Generative artificial intelligence has become part of knowledge-intensive professional services at a point when its capabilities seem to align with many key consulting tasks. Management consulting firms add value through analysis, interpretation, and problem-solving that is specific to each client; however, it is still unclear whether GenAI truly increases consulting productivity. This thesis focuses on how generative AI affects management consulting work processes and under what conditions task-level efficiency gains can translate into realised consulting productivity. The research method in this study is integrative literature review and thematic analysis of secondary empirical evidence, which include experimental studies of consulting-type tasks, surveys on generative artificial intelligence adoption, and industry reports. The findings suggest that GenAI delivers the clearest benefits in early-stage analysis and writing. Decision-making and problem-solving prove more challenging, as the same tool that performs well in some tasks can be unreliable in others. GenAI outputs can also appear polished despite flawed underlying reasoning, which makes verification an important part of responsible use. Higher consulting productivity does not follow automatically from task-level efficiency gains. Time savings need to be directed towards better analysis and sounder judgement to produce any real benefit. GenAI can support productivity in management consulting, but only when integrated deliberately into firm workflows, used within clear guidelines, and accompanied by consultant accountability for the final output. Liikkeenjohdon konsultointiyritykset tuottavat arvoa analyysin, tulkinnan ja asiakaskohtaisen ongelmanratkaisun kautta. Generatiivisesta tekoälystä on tullut osa konsultoinnin työprosessia, sillä se kykenee auttamaan useissa työn keskeisissä tehtävissä. Tässä tutkielmassa tarkastellaan, kuinka generatiivinen tekoäly vaikuttaa liikkeenjohdon konsultoinnin työprosesseihin ja millä edellytyksillä tehtävätason tehokkuushyödyt voivat muuttua työn tuottavuuden kasvuksi. Tutkimus perustuu integratiiviseen kirjallisuuskatsaukseen ja olemassa olevan empiirisen aineiston temaattiseen analyysiin. Aineisto koostuu kokeellisista tutkimuksista, generatiivisen tekoälyn käyttöä koskevista kyselytutkimuksista sekä toimialaraporteista, ja se nojaa erityisesti ihmisen ja tekoälyn yhteistyötä sekä asiantuntijatyön tuottavuutta käsittelevään kirjallisuuteen. Tutkimuksen perusteella selkeimmät tekoälyn hyödyt liittyvät varhaisen vaiheen analyyttisiin tehtäviin ja kirjoittamiseen, kun taas päätöksenteossa ja ongelmanratkaisussa vaikutukset ovat epäselvemmät. Tätä selittää niin sanottu epätasainen teknologinen rajapinta: sama työkalu voi toimia hyvin joissakin tehtävissä ja huonosti toisissa. Tekoälyn tuottama teksti voi myös vaikuttaa laadukkaalta, vaikka sen taustalla oleva analyysi olisi puutteellinen. Siksi tuotosten huolellinen tarkistaminen on kasvavissa määrin tärkeä osa konsultointityötä. Työn nopeutuminen tehtävätasolla ei automaattisesti tarkoita, että koko projekti muuttuu tuottavammaksi. Säästetty aika täytyy käyttää laadukkaampaan analyysiin ja asiakkaan tavoitteiden saavuttamiseen, jotta työstä tulee kokonaisuudessaan tuottavampaa.
Keywords: generative artificial intelligence; productivity; consulting; knowledge work; consultants; organisations (systems); artificial intelligence; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management